AN ACTION RESEARCH ON THE USE OF PERFORMANCE ASSESSMENT APPROACH IN SOCIAL STUDIES COURSES - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2011)
Primary curricula of Turkey have been gradually changed which is on the basis of constuctivist approach since 2005. The most of research which evaluated the implementation of new curricula indicate that there are some problems especially about the measurement and assessmet dimension of the new curricula. The purpose of this study is to examine what should be done to implement the performance assessment approach more effective in social studies courses and to determine students and teacher's views about this approach. Action research method was conducted mainly in three phases; the first phase included defining the problem, the second phase included developing, implementing and monitoring an action plan, the third phase included determining of the teacher and students' opinions about action plan and solutions were determined. The participants of the study consisted of a social studies teacher, and her 30 students attending seventh grade in Maltepe district of Istanbul. A semi-structured interviews, open-ended questionnaires, semi-structured observations, informal observations and interviews were conducted to gather the data. All data was analysed in conformity with qualitative descriptive data analysis. According to the general conclusions reached from the study, students evaluted the performance assessment tasks in terms of educational contributions such as providing enjoyable learning, working in groups, seeing the point and consolidate the information and to be memorable and instructive. Nevertheless, students also perceived this approaches as a problematic area because of structure of group work, inability to have particular skills, time problems, to be difficult and tiring, ect. The teacher regarded this approach as an ensuring the active participation of students, to be difficult, to have some disciplinary problems and necessity the balance of number of tasks. Findings were discussed in accordance with curriculum and its application and professional development.
Keywords: Performance assessment; alternative assessment; social studies courses